PH modulates interaction of 14-3-3 proteins with pollen plasma membrane H+ ATPases independently from phosphorylation. (1st September 2021) - Pertl-Obermeyer, Heidi; Gimeno, Ana; Kuchler, Verena; Servili, Evrim; Huang, Shuai; Fang, Han; Lang, Veronika; Sydow, Katharina; Pöckl, Magdalena; Schulze, Waltraud X; Obermeyer, Gerhard
Abstract : Phosphorylation of the pollen plasma membrane H + ATPase correlates with the start of tube germination and facilitates pH-dependent interaction with 14-3-3 proteins that regulate the H + ATPase. Abstract: Pollen grains transport the sperm cells through the style tissue via a fast-growing pollen tube to the ovaries where fertilization takes place. Pollen tube growth requires a precisely regulated network of cellular as well as molecular events including the activity of the plasma membrane H + ATPase, which is known to be regulated by reversible protein phosphorylation and subsequent binding of 14-3-3 isoforms. Immunodetection of the phosphorylated penultimate threonine residue of the pollen plasma membrane H + ATPase (LilHA1) of Lilium longiflorum pollen revealed a sudden increase in phosphorylation with the start of pollen tube growth. In addition to phosphorylation, pH modulated the binding of 14-3-3 isoforms to the regulatory domain of the H + ATPase, whereas metabolic components had only small effects on 14-3-3 binding, as tested with in vitro assays using recombinant 14-3-3 isoforms and phosphomimicking substitutions of the threonine residue. Consequently, local H + influxes and effluxes as well as pH gradients in the pollen tube tip are generated by localized regulation of the H + ATPase activity rather than by heterogeneous localized distribution in the plasma membrane.